2016
DOI: 10.1155/2016/3102481
|View full text |Cite
|
Sign up to set email alerts
|

Infants Actively Construct and Update Their Representations of Physical Events: Evidence from Change Detection by 12-Month-Olds

Abstract: The present research investigates the effects of top-down information on 12-month-olds’ representations of physical events, focusing on their ability to detect an object change across different events. Infants this age typically fail to detect height changes in events with tubes even though they successfully do so in events with covers. In Experiment  1, infants who saw a tube event in which objects did not interact successfully detected a change in an object’s height, suggesting that object interaction affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Because the present research examined the integration of psychological and physical reasoning in young infants, this juxtaposition might give rise to the worry that infants could fail in the inference condition, not because they were unable to track information gathered through inference, but because the procedure chosen was less than optimal for revealing their physical-reasoning capacity. In recent years, however, several reports have used a single-event, paused-scene procedure to study various facets of infants' physical reasoning, with no ill effects (Lin et al, 2021;Stavans & Baillargeon, 2018;Stavans et al, 2019;Wang & Goldman, 2016;. There was thus little apriori reason for concern, and the positive results of the inference condition confirmed that the procedure selected was appropriate for the present research.…”
Section: Methodsmentioning
confidence: 59%
“…Because the present research examined the integration of psychological and physical reasoning in young infants, this juxtaposition might give rise to the worry that infants could fail in the inference condition, not because they were unable to track information gathered through inference, but because the procedure chosen was less than optimal for revealing their physical-reasoning capacity. In recent years, however, several reports have used a single-event, paused-scene procedure to study various facets of infants' physical reasoning, with no ill effects (Lin et al, 2021;Stavans & Baillargeon, 2018;Stavans et al, 2019;Wang & Goldman, 2016;. There was thus little apriori reason for concern, and the positive results of the inference condition confirmed that the procedure selected was appropriate for the present research.…”
Section: Methodsmentioning
confidence: 59%
“…Because the present research examined the integration of psychological and physical reasoning in young infants, this juxtaposition might give rise to the worry that infants could fail in the inference condition, not because they were unable to track information gathered through inference, but because the procedure chosen was less than optimal for revealing their physical-reasoning capacity. In recent years, however, several reports have used a single-event, paused-scene procedure to study various facets of infants' physical reasoning, with no ill effects (Lin et al, 2021;Stavans & Baillargeon, 2018;Stavans et al, 2019;Wang & Goldman, 2016;. There was thus little apriori reason for concern, and the positive results of the inference condition confirmed that the procedure selected was appropriate for the present research.…”
Section: Methodsmentioning
confidence: 62%
“…Although the findings described above could potentially implicate preverbal recognition 157 of explanations, other evidence suggests that infants struggle to recognize explanations for 158 surprising events. For example, Wang & Goldman (2016) found that 12-month-old infants 159 successfully used information that was presented before a surprising event, such that they were 160 able to revise their expectations of the event's outcome. In contrast, when the same information 161 was presented after the event-thereby providing an explanation for what had already 162 happened-infants seemed unable to integrate this new information into their event 163…”
Section: Introduction 39mentioning
confidence: 99%